The antioxidant and antiproliferative activities of methanolic extracts from Njavara rice bran - Babu Phanithi P; Reddy Sareddy G; Rao Akiri SVC; Reddy Attipalli R (BMC, 2010)
Abstract Background Free radical-induced oxidative stress is the root cause for many human diseases. Naturally occurring antioxidant supplements from plants are vital to counter the oxidative damage in cells. The main objective of the present study was to characterize the antioxidant and antiproliferative potential of rice bran extracted from an important Indian rice variety, Njavara and to compare the same with two commercially available basmati rice varieties: Vasumathi, Yamini and a non medicinal variety, Jyothi. Methods Methanolic extracts of rice bran from four varieties; Vasumathi, Yamini, Jyothi and Njavara were used to study their total phenolic and flavonoid contents, in vitro antioxidant activities including total antioxidant activity, scavenging of nitric oxide and 1,1-Diphenyl-2-picrylhydrazyl (DPPH) radical, reducing power and cytotoxic activity in C6 glioma cells. Correlation coefficient and regression analysis were done by using Sigmastat version 3.1 and Stata statistical package respectively. Results Rice bran methanolic extract from Njavara showed the highest antioxidant and cell cytotoxic properties compared to the other three rice varieties. IC50 values for scavenging DPPH and nitric oxide were in the range of 30.85-87.72 μg/ml and 52.25-107.18 μg/ml respectively. Total antioxidant activity and reducing power were increased with increasing amounts of the extract. Total phenolic and flavonoid contents were in the range of 3.2-12.4 mg gallic acid-equivalent (GAE)/g bran and 1.68-8.5 mg quercetin-equivalent (QEE)/g bran respectively. IC50 values of cytotoxic assay (MTT assay) were 17.53-57.78 μg/ml. Correlation coefficient and regression analysis of phenolic content with DPPH and NO scavenging, MTT (-[4,5-dimethylthiazol-2-yl]-2,5-diphenyl tetrazolium bromide) assay, total antioxidant assay and reducing power showed a highly significant correlation coefficient values (96-99%) and regression values (91-98%). Conclusion The results of the present study show that the crude methanolic extract from Njavara rice bran contains significantly high polyphenolic compounds with superior antioxidant activity as evidenced by scavenging of free radicals including DPPH and NO. Njavara extracts also showed highest reducing power activity, anti-proliferative property in C6 glioma cells. In conclusion, it is conceivable that the Njavara rice variety could be exploited as one of the potential sources for plant - based pharmaceutical products.